2017
DOI: 10.3233/mgc-160225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes on calcium carbonate/calcium silicate phase and morphology

Abstract: The composition and microstructure of different CaCO3-Ca2SiO4-carbon nanotube composites have been studied. Materials have been characterized by X-ray diffraction (XRD), high resolution scanning electron microscopy (SEM), thermogravimetric/differential thermal analysis (TG/DTA), and Fourier-transform infrared (FTIR) spectroscopy. The morphology and structure of the inorganic systems are affected by the presence of multiwall carbon nanotubes (MWCNT) during the hydration processes and the nature of the MWCNT/SDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It was indicated that the calcium carbonate formed in the blank is calcite, and the 104 crystal plane is its main growth surface. For the calcium carbonate crystals formed in the solution containing carbon nanoparticles, most of the diffraction peaks of calcite disappeared and the characteristic peaks of aragonite appeared at 26.1°, 27.1°, 33.0°, 36.0°, 37.8°, 38.5°, 42.8°, 45.7°, 48.3°, 50.1°, 52.3°, and 52.9° corresponding to the (111), (021), (012), (200), (031), (112), (220), (221), (202), (132), and (231) crystal faces of aragonite [ 32 , 41 , 42 ]. This indicates that the presence of carbon nanoparticles transformed the main crystal form of calcium carbonate from calcite to aragonite, which is consistent with the SEM and FTIR results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that the calcium carbonate formed in the blank is calcite, and the 104 crystal plane is its main growth surface. For the calcium carbonate crystals formed in the solution containing carbon nanoparticles, most of the diffraction peaks of calcite disappeared and the characteristic peaks of aragonite appeared at 26.1°, 27.1°, 33.0°, 36.0°, 37.8°, 38.5°, 42.8°, 45.7°, 48.3°, 50.1°, 52.3°, and 52.9° corresponding to the (111), (021), (012), (200), (031), (112), (220), (221), (202), (132), and (231) crystal faces of aragonite [ 32 , 41 , 42 ]. This indicates that the presence of carbon nanoparticles transformed the main crystal form of calcium carbonate from calcite to aragonite, which is consistent with the SEM and FTIR results.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have also reported that the increase in the calcium ion concentration in the solution will have a greater impact on the experimental results. Surface-activated multiwall carbon nanotubes (MWCNTs) can serve as templates for calcium silicate growth [ 32 ] and the addition of MWCNTs could control the morphology of Ca 2 SiO 4 formed by CaCO 3 and silicic acid. Some carbon nanomaterials, such as modified water-soluble carbon nanomaterials, hydroxylated single-walled carbon nanotubes (HO-SWNTs), and isophthalic acid functionalized-SWNTs, could alter the morphology of the deposited CaCO 3 crystals [ 33 ], but the purified single-walled carbon nanotubes (SWNTs) could not exert an effect on both the phase and morphology of CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the mechanical properties of MTA were significantly improved with the addition of multi-walled carbon nanotube (Sanaee et al, 2019). In another study, the composition and microstructure of different calcium carbonate-calcium silicatecarbon nanotube composites have been studied (Gomez et al, 2017). Another chemical element with favorable biological properties is niobium that has been used in titanium alloys of endosseous implants, because of its excellent biocompatibility (Ward et al, 1996) and bioactive potential (Karlinsey et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…The strategy used here may contribute to broaden the use of functionalized MWCNTs with different hydrophilic molecules allowing to control selective in vitro crystallization of a variety of inorganic minerals. With this background in mind, we believe, on the one hand, that the selective chemical modification of MWCNTs may allow the control of the nucleation and growth of inorganic materials to achieve nanostructures with defined sizes, shapes, and compositions. , On the other hand, the kinetic aspects of in vitro CaOx crystallization using active modifier molecules at different concentrations and temperatures is the basis for in vivo assays and is the first approach for the urolithiasis medication. Indeed, for in vivo delivery of drugs, using implantable peristaltic mini pumps allows to foresee the classic problems such as solubility, concentration, control of small volume of release, and dose–response behavior to achieve a greater effect of pathological crystal inhibition using urolithiasis drugs.…”
Section: Introductionmentioning
confidence: 99%